Repeat intravenous r-tPA administration four days after initial thrombolytic therapy for recurrent ischemic stroke: A case report and review of literature - Aimen Vanood; Sunitha Santhakumar; Ahmad Said (Interdisciplinary Neurosurgery, 2021)
Stroke is a significant source of morbidity and mortality within the United States. The current standard of care for treatment of acute ischemic stroke is intravenous recombinant tissue-type plasminogen activator (IV r-tPA). However, IV r-tPA is contraindicated within 3 months of a previous stroke due to concern for symptomatic intracerebral hemorrhage (sICH). We describe the case of a 77-year-old female who developed aphasia and right-sided quadrantanopsia and was found to have a calcified embolus in the M3 branch of her left middle cerebral artery. She was given IV r-tPA with subsequent symptom resolution and no MRI evidence of acute or subacute infarct. 4 days after index stroke, she had recurrence of her symptoms, receiving a second dose of IV r-tPA. She improved clinically. Non-contrast CT 24 hours afterwards showed minimal foci of intraparenchymal hemorrhage without midline shift or mass effect. She remained neurologically stable and improved significantly with inpatient rehabilitation.